KEBIJAKAN DAN PENGEMBANGAN PEMBANGUNAN KARAKTER MELALUI PENDIDIKAN DI INDONESIA - Alawiyah, Faridah (Pusat Analisis Keparlemenan Badan Keahlian Sekretariat Jenderal DPR RI, 2012)
Indonesia is faced with crisis of moral issues that will hinder the development of the nation in the future. One solution to overcome this issue is through national policy of character education. However, the implementation of character education policy is stillfacing variety of problems. This is due to misunderstanding concepts of character ducation, character education policy, and the development of character education. This paper meant to give the description of concept of character and character education, character education policy in Indonesia, and also development of character education in formal, nonformal, and informal education.